GROWTH IMPROVEMENT OF TOMATO WITH THE APPLICATION OF BACTERIAL ISOLATES PRODUCING INDOLE ACETIC ACID (IAA) AND PHOSPHATE SOLUBILIZER - Eny Ida Riyanti; Dwi Ningsih Susilowati; Karden Mulya; Edy Listanto (Indonesian Agency for Agricultural Research and Development, 2019)
Soil bacteria have important roles in biogeochemical cycle for soil fertility and have been manipulated for ecologically-friendly crop production. The search for beneficial association between microbes and plants for promoting growth and health should be studied for tomato growth improvement. The study aimed to evaluate 19 microbial isolates which produced indole acetic acid (IAA) affecting growth and development of tomato (Palupi variety), and molecularly identify the most effective isolates in improving tomato growth based on 16s rDNA sequences. The experiment was conducted in pots using a complete randomized design with three replications. The parameters observed included plant height, plant dry weight, root length, root dry weight, and fruit fresh weight. The isolates that significantly improved tomato growth were molecularly identified using 16s rRNA sequence. The phenotypic properties such as IAA content and phosphate solubilizing index (PI) of the superior isolates were determined. Results showed that the application of bacterial isolates on tomato significantly increased plant dry weight and fruit yield. From 19 isolates tested, Aj 3.7.1.14 significantly increased plant dry weight, root length, and fruit yield. This isolate produced IAA of about 14.77 ppm and PI of 1.86. Molecular analysis on Aj 3.7.1.14 demonstrated that the isolate had 89% similarity to Pseudomonas fragi. The identified P. fragi was found to be the most effective isolate for improving tomato growth and fruit yield. Another isolate, Bacillus amyloliquefaciens was found to promote root length, root dry weight, and fruit yield. These isolates are potential to be further investigated for field trials